Redox regulation of cancer cell migration and invasion - Tochhawng, L.; Deng, S.; Pervaiz, Shazib; Yap, C. (Elsevier, 2013)
Cancer cell migration and invasion are the initial steps in metastasis. Through a series of cellular events, including cytoskeletal remodeling resulting in phenotype changes and degradation of the extracellular matrix, cells are able to detach from the primary tumor and metastasize to distant sites. These changes occur in response to intracellular signaling mechanisms triggered via cell surface receptor stimulation or signal amplification within the cell. Amongst the active molecules that participate in relaying cellular signals are the reactive oxygen species (ROS). Initially identified to participate in defense mechanisms to ward off invading pathogens, ROS are now considered to have important roles in several other biological processes including cancer development. In this report, we review recent evidence pointing towards the involvement of ROS in tumor progression. We discuss the biology of ROS and their roles at different stages during the process of cancer cell migration and invasion. © 2012 Elsevier B.V. and Mitochondria Research Society.